Rekonseptualisasi Penyelesaian Perselisihan Hasil Pemilihan Umum di Indonesia - Jayus Jayus (Jurnal Konstitusi, 2013)
Elections are the means to implement sovereignty of the people in order to  elect members of the House of Representatives, Regional Representatives Council, Local  Legislative  Council,  the  President  and  Vice  President.  Election  are    also meaningful for selecting the leader of the nation and the state (public officials) and as community control over board membership, President and Vice President to come. Election results are manifestation of popular sovereignty, which can lead to a dispute between organizer and election participants either political parties or individuals. The result of which can be challenged legally by election participant. The participant can also request the cancellation of the election result to the agency given with the authority to decide. Conceptually, the right institution to decide on election dispute is a special ad hoc election court. Constitutionally, dispute resolution of election result is intended to protect citizens' constitutional rights.